PROFIL USAHA MINYAK ATSIRI PALA UD. WIDIA MANDIRI DI DESA TREMAN - Paris Loziner Edison Sirait; Ventje V. Rantung; Lyndon R.J. Pangemanan; Jean F.J. Timban (Universitas Sam Ratulangi, 2013)
ABSTRACTThe objective of this research was to determine the profile of the business nutmegessential oil. This study used primary data obtained through interview techniques directly tobusiness owners using a list of questions were primarily production and cost. The methodanalysis was a descriptive analysis and presented in tables. Other analysis was costs, revenues,profits, and ratio of R/C.The results of this research indicated that the efforts of nutmeg essential oil